Further Studies on the “Dynia” Clotting Abnormality - Pechet, L; Cochios, F; Deykin, D (Thrombosis and Haemostasis, 1967)
1. One patient with multiple bleeding episodes and 4 asymptomatic relatives in 3 generations reveal a coagulation abnormality that cannot be attributed to any known coagulation factor deficiency or to a circulating inhibitor. The abnormality is characterized by deficient generations of intrisic thromboplastin and intermediate product I, and can be corrected by normal plasma and serum.2. The ability of normal blood to correct the coagulation defect in vitro is heat labile; it is not removed from plasma by adsorption with BaSO4 or Al(OH)3. Neonatal blood and blood taken from patients either receiving coumarin drugs or with severe liver disease sustain the ability to correct the described defect. Ox, rabbit and dog blood are also corrective.3. The finding of normal factors XII, XI and IX activities, as well as normal serum thrombosis accelerator (STA) activity, places this abnormality beyond the stage of factor IX activation.4. The data suggest that the familial coagulation abnormality is located in the clotting sequence either in the activation of factor VIII, or in the activation of factor X by factor VIII. Either interpretation is in agreement with the finding of abnormal intermediate product I generation, which reflects primarily the intrinsic activation of factor X.5. The frequency of this defect is unknown. Conceivably some patients considered to have factor XI (PTA) deficiency because of a plasma and serum correctable defect in their thromboplastin generation, may actually have a coagulation defect similar to that described in the Dynia family.6. It is suggested that the name “Dynia defect” be temporarily assigned to this clotting abnormality.